Sexual Science as Manifested in Hardy's Marriage Plot - Ahmad, Asma Hana (2003)
This study starts with the exploration of Darwin's theory of 'Natural Selection' also known as 'Survival of the Fittest' (based on The Origin of Species). The exploration continues with the discussion on 'Sexual Selection'. Darwin' s theory is investigated through the creative works of Thomas Hardy. The novels chosen for discussion are from the Wessex novels. The Woodlanders (1887) introduces the sense of struggle in nature as well as in characters; Tess of the D'Urbervilles (1891) represents the endless struggle of an unfortunate victim due to cruel environment; and finally, Jude the Obscure (1895) attacks the institutional law of marriage. The investigation mostly focuses on his marriage plot. Darwin's theory works towards establishing the defining features of struggle in Hardy' s characterisation and structure of each text with regards to sexuality. The nature of human evolution may be considered as the underlying theme in relation to the themes of struggle with morality, sexuality, and marriage of Hardy's works. The exploration of the nature of human evolution through Hardy's work concomitantly relates to problematic relationship and marriage during the Victorian era while keeping in mind another underlying factor in Darwin's theory, that is, 'spiritual void' (the notion that God plays no role in the creation of different species). The behaviour of each character and the outcome of their action are explained scientifically. The survival of Hardy' s characters depends on their ability to adapt to their surrounding environment. The notion of 'adaptation' and 'maladaptation' to the environment are the reference points to understand the underlying forces of male and female sexuality in relation to marriage. The study'S focus on the individual struggle against the Victorian morality (concerning the relationship between man and woman) is based on Darwin's explanation on human sexual instinct versus Victorian orthodox law. This struggle could either result in a strong marriage that stays at the end of the novel or death of the protagonist. Death is a reoccurrence event in his work. Finally, this research concludes with the tragic death of each character and why he/she is unable to survive in his/her marriage.